Disruption of Earth’s Atmospheric Flywheel: Hothouse-Earth Collapse of the Biosphere and Causation of the Sixth Great Extinction - Whiteside, Mark; Herndon, J. Marvin (European Journal of Applied Sciences, 2024)
The Anthropocene is the Epoch of Man, in which human activities have drastically changed Earth’s geology, landscape, ecosystems, biodiversity and climate. The energy necessary to power modern civilization comes from petroleum, natural gas, and coal, the latter derived from millions of years of photosynthesized vegetation, subsequently stored underground. The best stratigraphic markers of the Anthropocene are combustion products of these fuels such as spherical carbonaceous particles and iron-containing magnetic particles. We have previously shown that particle pollution from combustion sources, not carbon dioxide, is the primary cause of global warming. More recently, we have shown combustion products, notably coal fly ash and HULIS aerosols, not chlorofluorocarbons, are the primary cause of stratospheric ozone depletion. Modern-day transformation of the biosphere is strikingly evident in the atmosphere, which has been polluted to the point of overcoming Earth’s atmospheric flywheel (radiation buffering mechanism). The planet is already in a Hothouse Earth phase, with runaway warming triggering multiple “tipping points” that threaten biosphere integrity and human civilization itself. Contrary to the prevailing narrative, the stratospheric ozone layer has been badly damaged, and increasingly deadly ultraviolet radiation now penetrates to Earth’s surface. This situation has been made unimaginably worse by the deliberate, covert planetary modification, euphemistically called geoengineering. While the scientific community, government leaders, the mainstream media, and indeed the masses “look the other way” and ignore the obvious atrocities in our skies, ongoing tropospheric aerosol geoengineering operations continue to spray toxic substances, such as coal fly ash, into the atmosphere. Humanity must wake up to the dire reality we face. International cooperation and crash efforts will be necessary to at least slow the rate of biosphere collapse and salvage something of our critical life support systems. Our time is short to phase out and end all geoengineering activities and to reduce and/or eliminate all sources of coal fly ash and HULIS-type aerosols.